2018
DOI: 10.1001/jamacardio.2017.5250
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Worsening Heart Failure as a Target for Therapy

Abstract: As the public health and economic burdens of heart failure continue to grow, recognizing the entity of outpatient WHF is critical. Efforts to reduce heart failure hospitalization should include developing effective therapies and care strategies for outpatient WHF. The outpatient WHF population represents a major opportunity for therapeutic advancements that could fundamentally change heart failure care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 69 publications
0
114
0
2
Order By: Relevance
“…Consistent with evolving practice in HF clinical trials and accumulating data suggesting similarly poor prognosis for worsening HF patients in the inpatient and outpatient care settings, we suggest CV outcome trials consider capture of worsening HF events (according to pre-specified criteria) irrespective of the location of care (including ambulatory clinics, urgent care facilities, emergency departments, and hospitals). (58,6062) Although such a procedure may carry a modest increase in trial cost and complexity, inclusion of the spectrum of worsening HF events may improve power for detecting therapeutic signals and would be congruent with trends among healthcare systems towards increasing emphasis on outpatient management of worsening HF to decrease costs associated with hospitalization. (62,63)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with evolving practice in HF clinical trials and accumulating data suggesting similarly poor prognosis for worsening HF patients in the inpatient and outpatient care settings, we suggest CV outcome trials consider capture of worsening HF events (according to pre-specified criteria) irrespective of the location of care (including ambulatory clinics, urgent care facilities, emergency departments, and hospitals). (58,6062) Although such a procedure may carry a modest increase in trial cost and complexity, inclusion of the spectrum of worsening HF events may improve power for detecting therapeutic signals and would be congruent with trends among healthcare systems towards increasing emphasis on outpatient management of worsening HF to decrease costs associated with hospitalization. (62,63)…”
Section: Discussionmentioning
confidence: 99%
“…(58,6062) Although such a procedure may carry a modest increase in trial cost and complexity, inclusion of the spectrum of worsening HF events may improve power for detecting therapeutic signals and would be congruent with trends among healthcare systems towards increasing emphasis on outpatient management of worsening HF to decrease costs associated with hospitalization. (62,63)…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority of WHF patients experience rapid and severe deterioration leading to an immediate emergency department (ED) presentation. 7 By contrast, most experience gradual worsening of signs and symptoms over a more extended period, an observation further supported by invasive monitoring showing gradual increases in filling pressures days to weeks before onset of worsening symptoms and hospital presentation. 14 Likewise, markers of organ injury are not specific to the hospital stay.…”
Section: Reassessing the Impact Of Heart Failure Hospitalization: A Mmentioning
confidence: 94%
“…7 Multiple analyses from clinical trial cohorts have found WHF patients treated in the outpatient setting to have subsequent mortality similar to hospitalized populations. 810 Importantly, these studies suggest that clinical characteristics, rather than location of care or recentness of hospitalization, are the dominant determinants of risk.…”
mentioning
confidence: 99%
“…These findings are consistent with reports highlighting the subacute nature of many worsening HF episodes and potential influences of non-biologic factors (e.g., country-specific and local healthcare infrastructure/resources, financial incentives, patient preferences) in dictating exact timing or occurrence of HF hospitalization. 9 Nonetheless, noting that NYHA class at randomization was more severe among patients randomized earlier in ASTRONAUT, early in-hospital enrollment may be preferable for trials focused on short-term symptomatic improvement with in-hospital endpoints (e.g., dyspnea relief).…”
mentioning
confidence: 99%